Calcium-Dependent Protein Kinases from Arabidopsis Show Substrate Specificity Differences in an Analysis of 103 Substrates - Curran, Amy; Chang, Ing-Feng; Chang, Chia-Lun; Garg, Shilpi; Miguel, Rodriguez M.; Barron, Yoshimi D.; Li, Ying; Romanowsky, Shawn; Cushman, John C.; Gribskov, Michael; Harmon, Alice; Harper, Jeffrey F (Frontiers in Plant Science, 2011)
The identification of substrates represents a critical challenge for understanding any protein kinase-based signal transduction pathway. In Arabidopsis, there are more than 1000 different protein kinases, 34 of which belong to a family of Ca2+-dependent protein kinases (CPKs). While CPKs are implicated in regulating diverse aspects of plant biology, from ion transport to transcription, relatively little is known about isoform-specific differences in substrate specificity, or the number of phosphorylation targets. Here, in vitro kinase assays were used to compare phosphorylation targets of four CPKs from Arabidopsis (CPK1, 10, 16 and 34). Significant differences in substrate specificity for each kinase were revealed by assays using 103 different substrates. For example CPK16 phosphorylated Serine 109 in a peptide from the stress-regulated protein, Di19-2 with KM ~70 µM, but this site was not phosphorylated significantly by CPKs 1, 10, or 34. In contrast, CPKs 1, 10, and 34 phosphorylated 93 other peptide substrates not recognized by CPK16. Examples of substrate specificity differences among all four CPKs were verified by kinetic analyses. To test the correlation between in vivo phosphorylation events and in vitro kinase activities, assays were performed with 274 synthetic peptides that contained phosphorylation sites previously mapped in proteins isolated from plants (in vivo-mapped sites). Of these, 74 (27%) were found to be phosphorylated by at least one of the four CPKs tested. This 27% success rate validates a robust strategy for linking the activities of specific kinases, such as CPKs, to the thousands of in planta phosphorylation sites that are being uncovered by emerging technologies.